2013
DOI: 10.1016/j.ijscr.2013.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic retained foreign body in the right atrium. Lessons to Learn

Abstract: INTRODUCTIONWe report a case of a retained foreign body in the right atrium and the review of the literature discussing several cases where the poor attention and management of medical staff has led to worsening consequences to patient's health.PRESENTATION OF CASEIn our case the mass demonstrated on MRI scan turned out to be an inflammatory process and organized clotted blood built around a broken piece of a plastic cannula protruding out of the right atrium. This caused debilitating pleuritic pain to the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Interestingly, patients may remain asymptomatic for some time before constitutional signs and symptoms begin to appear as in our case 2. Choi et al 2 described a case where they found a plastic cannula protruding out of the RA months after an invasive procedure.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Interestingly, patients may remain asymptomatic for some time before constitutional signs and symptoms begin to appear as in our case 2. Choi et al 2 described a case where they found a plastic cannula protruding out of the RA months after an invasive procedure.…”
Section: Discussionmentioning
confidence: 70%
“…Choi et al 2 described a case where they found a plastic cannula protruding out of the RA months after an invasive procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Much less frequently, it is the consequence of medical procedures, including blood vessel cannulization (7,8). In the studied case, the foreign body -a The medical treatment in case of a foreign body in the heart is individualized in each case and depends on the type and size of the body, the route of its entry and the localization in the heart as well as on possible concomitant symptoms (2,3,10). It is said that foreign bodies embedded in the myocardium or pericardium of non-symptomatic patients should be monitored (1,(3)(4)(5)9).…”
Section: Discussionmentioning
confidence: 99%
“…Other devices may have been left in the heart or may have been dislodged and can be asymptomatic or cause devastating complications such as Candida endocarditis of the tricuspid valve or a broken stylet retained in the interatrial septum …”
Section: Discussionmentioning
confidence: 99%
“…35 Severe tricuspid regurgitation with right heart failure occurred due to damage of the tricuspid valve with a migrated Wallstent in 2 cases. 34,40 Other devices [41][42][43][44][45][46][47][48][49] may have been left in the heart or may have been dislodged and can be asymptomatic or cause devastating complications such as Candida endocarditis of the tricuspid valve 45 or a broken stylet retained in the interatrial septum. 13 Percutaneous vertebroplasty is an effective, minimally invasive procedure for the treatment of osteoporotic and metastatic vertebral fractures.…”
Section: Discussionmentioning
confidence: 99%